A shared boundary object: Financial innovation and engineering in Islamic financial institutions. Issue 3 (May 2021) - Alamad, Samir; Hidayah, Nunung Nurul; Lowe, Alan
Abstract: This paper explores the way in which ethico-faith-based rules act as a boundary object in constraining the process of financial innovation and engineering (FIE) in Islamic Financial Institutions (IFIs). The paper examines how this faith-based approach is enacted in the FIE process amid different social worlds and groups that cooperate without consensus within IFIs. We contribute to studies of governance in faith-based organizations, by identifying the plasticity of faith-based rules that act as boundary objects in the governance of the FIE process. The plasticity of ethico-faith based rules allows coordination among local and global actors with intersecting faith-based values, logics, and interests. IFIs ensure that the products of FIE become an integral part of and as compatible as possible with the logics of global financial markets.